Implementation Of Village-Owned Enterprises (BUMDes) “Bersama Sei Rampah” In Firdaus Village Sei Rampah District Serdang Bedagai Regency - Onny Medaline; T. Riza Zarzani; Merry Agnes (International Journal of Society and Law, 2023)
The urgency of the establishment of the Village Law is to empower the villagers who make the village able to develop itself with its potential. To achieve national development, the village is a leading government agency that can reach groups that want to be prosperous by forming BUMDes. Strengthening the independence of the village through this law also places the village as the subject of government and development that really departs from the bottom (bottow up). Improving the welfare of villagers against the backdrop of the establishment of strong BUMDes in accordance with the objectives and principles of social justice which is a basic state value in Indonesia. The formulation of the problem that will be the subject of discussion, is: How is the implementation of BUMDes in Firdaus Village? This research is empirical legal research, In this study the authors analyzed primary data and secondary data to review the implementation of Village Owned Enterprises located in Firdaus Village Sei Rampah District Serdang Bedagai Regency. In this study it can be concluded that the implementation of BUMDes has been running quite well which is illustrated by the development of BUMDes from year to year and in line with the awareness of the village community in utilizing the existence of BUMDes.